Determinan Audit Report Lag dengan Spesialisasi Industri Auditor sebagai Moderator - Nurfauziah, Tiya (MASINTAN ACCOUNTANCY RESEARCH, 2026)
Research aims: This study aims to analyze the effect of audit tenure, KAP size and auditor turnover variables on audit report lag with auditor industry specialization as the moderating variable in companies listed on the Indonesia Stock Exchange. Design/Methodology/Approach: The data used in this research was secondary data. Sampling in this study was conducted by using a purposive sampling method with 36 companies that met the criteria for testing. This study applied statistical testing and data processing by using WarpPLS 6.0 Research findings: The result of this study indicated that: (1) Audit Tenure had a negative effect on Audit Report Lag, (2) KAP Size had no effect on Audit Report Lag, (3) Auditor Turnover had no effect on Audit Report Lag, (4) Auditor Industry Specialization moderated the negative effect of Audit Tenure on Audit Report Lag, (5) Auditor Industry Specialization did not moderate the effect of KAP Size on Audit Report Lag, (6) Auditor Industry Specialization was not able to moderate the effect of Auditor Turnover on Audit Report Lag. Theoretical contribution/Originality: This study contributes to the literature on audit report lag by examining the role of auditor industry specialization as a moderator of the relationship between firm characteristics and the timeliness of audit completion. Practitioner/Policy implication: The findings provide useful guidance for companies, auditors, and regulators. For companies, the results support hiring auditors who understand their industry well to make audits more efficient and speed up the release of financial reports. For public accounting firms, the study shows the need to develop industry knowledge to improve audit quality and speed. For regulators and market authorities, the findings can help guide policies that encourage auditor skills in specific industries, supporting clear, timely financial reporting and smooth markets.